Los corridos prohibidos como narrativa de la violencia en Colombia: un análisis de la producción bibliográfica de Iberoamérica entre 1997 y 2020 (2021)
The purpose of the following compilation monograph is to identify Ibero-American documents around the prohibited corridos as a narrative of the context of violence and drug trafficking in Colombia, where it was possible to extract the different perspectives, objective methodologies and conclusions used by authors who investigated this topic among the years 1997 and 2020, because on this date (19979 the first musical production of prohibited corridos in Colombia was launched by producer Alirio Castillo